2015
DOI: 10.1159/000368562
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Contact Points on the Performance of Caries Detection Methods in Approximal Surfaces of Primary Molars: An in vivo Study

Abstract: This in vivo study aimed to evaluate the influence of contact points on the approximal caries detection in primary molars, by comparing the performance of the DIAGNOdent pen and visual-tactile examination after tooth separation to bitewing radiography (BW). A total of 112 children were examined and 33 children were selected. In three periods (a, b, and c), 209 approximal surfaces were examined: (a) examiner 1 performed visual-tactile examination using the Nyvad criteria (EX1); examiner 2 used DIAGNOdent pen (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 28 publications
3
29
2
2
Order By: Relevance
“…Radiographic examination had the lowest sensitivity at the (D 1 ) level of diagnosis which agrees with the findings of previous studies . Although histological examination showed 35% of surfaces to have enamel caries, radiographic examination showed only 11% of the surfaces to have enamel caries which shows that radiographic examination was only able to detect less than one‐third of the enamel lesions.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Radiographic examination had the lowest sensitivity at the (D 1 ) level of diagnosis which agrees with the findings of previous studies . Although histological examination showed 35% of surfaces to have enamel caries, radiographic examination showed only 11% of the surfaces to have enamel caries which shows that radiographic examination was only able to detect less than one‐third of the enamel lesions.…”
Section: Discussionsupporting
confidence: 89%
“…For these reasons, temporary tooth separation (TTS) is used by some clinicians for the detection of proximal caries and this adjunct to visual examination has been shown to be useful in identifying dental caries in the proximal surfaces of permanent premolars and molars and of primary molars …”
Section: Introductionmentioning
confidence: 99%
“…Lussi and Hellwig (65) reported that its performance was similar to the traditional LF on occlusal surfaces. Ribeiro et al (66) compared the performance of visual examination, bitewing radiography, and LF pen for detection of approximal caries on primary teeth in vivo, and micro CT after tooth exfoliation served as the gold standard (66). Before tooth separation, the LF pen demonstrated higher Sn and lower Sp than visual and bitewing radiographic examinations for detection of enamel caries.…”
Section: Laser Fluorescence (Lf)mentioning
confidence: 99%
“…After tooth exfoliation, in vitro LF pen examination was performed and improved Sn and Sp for both enamel and dentinal lesions was observed. This could be because the laser light could now directly access the tooth surface (66). A systematic review of LF (67) concluded that it exhibited higher Sn than other traditional diagnostic methods.…”
Section: Laser Fluorescence (Lf)mentioning
confidence: 99%
“…Mendes et al speculated that the combined strategies could perform better in permanent teeth with a higher prevalence of non-evident caries lesions [10]. Nevertheless, most of the studies do not recommend the use of the LF or LF pen for permanent or primary teeth as the gold standard or sole diagnostic tool for occlusal caries detection [4, 39, 44, 45] or approximal caries detection [4] diagnostic tool to be used in combination with visual diagnostic techniques and/or radiography to assist the clinician when making operative decisions [46]. …”
Section: Discussionmentioning
confidence: 99%